Phenomenon of loss of heterozygosity in tumour tissue of breast cancer: association with expression of monoresistance genes - M. M. Tsyganov; I. V. Deryusheva; E. Yu. Garbukov; M. K. Ibragimova; P. V. Kazantseva; V. A. Bychkov; E. M. Slonimskaya; N. V. Litviakov (Бюллетень сибирской медицины, 2018)
Purpose of work. To perform a genome-wide association study of loss of heterozygosity (LOH) with monoresistance genes expression during neoadjuvant chemotherapy (NAC) in breast cancer.Materials and methods. The study involved 68 patients with breast cancer. The tumour stages were IIAIIIB. RNA was extracted from tissue specimens (before and after NAC) using RNeasy Plus mini Kit (Qiagen, Germany). Expression profiling of the RRM1, ERCC1, TOP1, TOP2a, TUBB3, TYMS, BRCA1 genes was carried out using quantitative real-time PCR (qPCR). DNA was extracted from 68 biopsy specimens of tumour tissues using QIAamp DNA mini Kit (Qiagen, Germany). LOH status was detected using microarray analysis using high density DNA-chip manufactured by Affymetrix CytoScanTM HD Array company.Results. As a result of the study of loss of heterozygosity was evaluated in 13815 genes. The frequency of LOH varied from 0% to 63%. The highest incidence of heterozygosity loss events is characteristic for genes of 16, 17 and the X-chromosome. Our study established that the phenomenon of loss of heterozygosity in monoresistance genes (BRCA1, ERCC1, RRM1, TOP1, TOP2A, TUBB3 and TYMS), is not associated with their level of expression in the tumor. A statistical association has been found between LOH and level of expression of the studied genes in 54 genes. Among them it is necessary to note genes encoding miRNA and «zinc fingers» involved in the regulation of transcription of many genes, transmembrane drug transporters and ion channels, genes of the MAP kinase signaling pathway, and others.Conclusion. The results of this study allow for the more exact determination of the expression picture of monoresistance genes in the tumor and the indication of new candidate genes which are involved in the regulation of the expression of these genes. Evaluation of the loss of heterozygosity in tumor tissue can be used as an additional criterion for personalizing chemotherapy.